Enhanced Interfacial Charge Transfer and Separation Rate based on Sub 10 nm MoS2 Nanoflakes In Situ Grown on Graphitic‐C3N4. Issue 13 (27th May 2019) - Wu, Haoran; Qian, Yongteng; Cui, Jing; Chai, Qingqing; Du, Jimin; Zhang, Linyu; Zhang, Huijun; Wang, Weimin; Kang, Dae Joon
Abstract: Herein, sub 10 nm MoS2 nanoflakes are successfully in situ grown on graphitic‐carbon‐nitride (MoS2 /g‐C3 N4 ) through a hydrothermal strategy. The scanning electron microscopy result indicates that the thickness of the MoS2 nanoflakes is less than 10 nm, which can boost the transport rate of the photoproduced charge during the photodegradation process. Transmission electron microscopy result clearly shows that an excellent interfacial heterojunction is formed between g‐C3 N4 and MoS2, which will significantly improve the stability of catalysts. Particularly, the optimal 8% MoS2 /g‐C3 N4 product displays significantly enhance catalytic performance and excellent long‐term photodurability. These superior photocatalytic properties are attributed to the excellent interfacial heterostructure between MoS2 and g‐C3 N4, which extends the visible light absorption range, suppresses the recombination, and improves the transfer rate of photoproduced charge. Abstract : The MoS2 /g‐C3 N4 heterostructures are fabricated by a cost‐effective strategy. Such heterostructures show the superior photocatalytic activity for degradation of rhodamine B under the visible light irradiation since the sub 10 nm MoS2 nanoflakes grown on g‐C3 N4 can not only offer numerous surface reactive sites but also boost the transport rate of the photoproduced charge during the photodegradation process.